Molecular phylogeny of the New World gecko genus Homonota (Squamata: Phyllodactylidae) - Morando, Mariana (2014)
The genus Homonota was described by Gray (1845) and currently includes 10 species: Homonota andicola, H. borellii, H. darwinii, H. fasciata, H. rupicola, H. taragui, H. underwoodi, H. uruguayensis, H. williamsii & H. whitii and one subspecies of H. darwinii (H. darwinii macrocephala). It is distributed from 15° latitude south in southern Brazil, through much of Bolivia, Paraguay, Uruguay and Argentina to 54° south in Patagonia and across multiple different habitats. Several morphological taxonomic studies on a subset of these species have been published, but no molecular phylogenetic hypotheses are available for the genus. The objective of this study is to present a molecular phylogenetic hypothesis for all the described species in the genus. We sequenced two mitochondrial genes (cyt-b & 12S: 1745 bp), seven nuclear protein coding (RBMX, DMLX, NKTR, PLRL, SINCAIP, MXRA5, ACA4: 5804 bp) and two anonymous nuclear loci (30Hb, 19Hb: 1306 bp) and implemented traditional concatenated analyses (MP, ML, BI) as well as species-tree (*beast) approaches. All methods recovered almost the same topology. We recovered the genus Homonota as monophyletic with strong statistical support. Within Homonota, there are three strongly supported clades (whitii, borellii and fasciata), which differ from those previously proposed based on scale shape, osteology, myology and quantitative characters. Detailed morphological analyses based on this highly resolved and well-supported phylogeny will provide a framework for understanding morphological evolution and historical biogeography of this phenotypically conservative genus. We hypothesize that extensive marine transgressions during Middle and Late Miocene most probably isolated the ancestors of the three main clades in eastern Uruguay (borellii group), north-western Argentina-southern Bolivia (fasciata group), and central-western Argentina (whitii group). Phylogeographic and morphological/morphometric analyses coupled with paleo-niche modelling are needed to better understand its biogeographical history.